An Audit of primary ovarian pregnancy in a tertiary care hospital - Chanu, Sairem Mangolnganbi; Dey, Biswajit; Rudrapal, Gourisankar; Panda, Subrat; Raphael, Vandana; Singh, Ahanthem Santa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ovarian pregnancy is uncommon form of ectopic pregnancy with increasing trend in its incidence. Various risk factors have been implicated like intrauterine contraceptive devices, fertility treatments, pelvic inflammatory disease (PID), and endometriosis. Methods: This is a retrospective observational study done over a period of 10 years from January 2008 to December 2017.All the patients, who were diagnosed as primary ovarian pregnancy based on Spielberg’s criteria, were included in the study. Results: There were 6 cases (6.3%) of primary ovarian pregnancy out of the 95 cases of ectopic pregnancies. The age of the patients ranged from 28 years to 43 years with a mean age of 31.8 years. Amenorrhea and acute pain abdomen was present in all the patients. Laparotomy was done in all the cases. Excision of the sac with partial ovariectomy was done in 2 cases (33.3%).Oophorectomy with salpingectomy was done in the rest of the 4 cases (66.7%). Histopathological confirmation was done in all the cases. Conclusions: Ovarian pregnancy is uncommon form of ectopic pregnancy with increasing trend in its incidence. Management of choice is laparoscopy. Laparotomy is done if there are signs of rupture.